808 nm-light-excited upconversion nanoprobe based on LRET for the ratiometric detection of nitric oxide in living cancer cells. Issue 22 (30th May 2018) - Wang, Han; Liu, Yi; Wang, Zhaohui; Yang, Man; Gu, Yueqing
Abstract : NO (nitric oxide) has dual functions in cancer, promoting carcinogenesis in low concentrations and inducing tumor cell apoptosis at high concentrations. Abstract : NO (nitric oxide) has dual functions in cancer, promoting carcinogenesis in low concentrations and inducing tumor cell apoptosis at high concentrations. The dual-edged-sword functions of NO make it particularly appealing to develop a sensitive and specific chemical probe for its detection. However, most NO sensors suffer from poor Stokes shifts and are limited by ultraviolet (UV) or visible light excitation, which render it difficult to avoid the intrinsic background signal. In this study, an 808 nm laser-excited Nd 3+ -sensitized upconversion nanoprobe based on LRET (luminescence resonance energy-transfer) for NO detection was constructed for the first time. This probe was composed of Nd 3+ -sensitized core–shell upconversion nanoparticles (540 nm and 660 nm emission) as the energy donor and RhBs as the acceptor. In the presence of NO, RhBs was converted into Rhodamine B and its strong absorption subsequently quenched the 540 nm fluorescence of UCNPs, while the emission at 660 nm remained constant. The ratiometric detection of the fluorescence at 540 nm, as compared to 660 nm, can precisely respond to the difference in NO levels with a detection limit of 0.21 μM. Importantly, compared with conventional UCNPs excited at 980 nm, the 808 nm light excitation led to lower water absorption and deeper tissue penetration, thus avoiding overheating and allowing for long-term biological imaging. This strategy has been perfectly applied to detecting the NO levels in living cells to differentiate the tumor cells from normal cells based on varied intracellular NO concentration. Further, the nanosystem realized the real-time monitoring of NO during treatment with NO donor drugs, which could inspire the future application of this probe to guide NO therapy.